MANAJEMEN FESTIVAL DI KOTA SOLO STUDI KASUS PADA SOLO KARNAVAL, SOLO INTERNATINAL PERFORMING ARTS, SOLO BATIK CARNIVAL, DAN SOLO MENARI - Utami, Fawarti Gendra Nata (Acintya, 2016)
This research aims to develop learning in the field of performing arts management, considering in particular the art of research on the management of the festival is still very minimal done. While the activities of management and arts management are the main things that must be considered and doneas early as possible beyond the artistic issues a mat or platform. Management is not only about management cramped funds to prepare and present a performance but more complex than that. Performing arts festival is an artistic event that needs special handling, careful planning and extensivework area and involves a lot of team work. Many important how a festival it is important to be held or carried. Many big questions that must be answered; about whether the festival was real? to whom the festival is reserved, what his Goal of the festival was held, what the target of the festival is held? Whatcarried the theme? discourse, there are many more issues. Zoning of rising fund or fund-raising, supporting the government, community involvement and community, artistic strong board, and not less important is the issue of management audience. Management of the audience is important becausethe festival is always synonymous with audiences on a large scale and even thousands on this issue is often not handled properly and tend to be unthinkable. And Solo is important because in addition to being a city of culture, city and town dance festival. Besides getting a concrete picture of the variousfestivals held in the city of Solo of course with the advantages and disadvantages of each, we also had the opportunity to discusses the discourse and the problems that occur in organizing a festival event. To the researchers will look and unravel some of the major festivals held in the city of Solothem; Carnival Solo, Solo Batik Carnival, Solo International Performing Arts, and solo dancing. Besides getting a concrete picture of the various festivals in the city of Solo, which of course with the advantages and disadvantages of each, we also had the opportunity to discusses the discourse and the problems that occur in the organization of a festival.Keywords: Management, Festival, Solo.